HamFET: A High-Performance Subthermionic Transistor Through Incorporating Hybrid Switching Mechanism - Qianqian Huang; Shaodi Xu; Ru Huang (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
Field-effect transistors (FETs) switched by quantum band-to-band tunneling (BTBT) mechanism, rather than conventional thermionic emission mechanism, are emerging as an exciting device candidate for future ultralow-power electronics due to their exceptional electronic properties of subthermionic subthreshold swing. However, fundamental limitations in drive current have hindered such technology encountering for high-performance and high-speed operations, especially for silicon-based device. Here, we demonstrate a novel pathway of integrating tunneling and thermionic emission mechanisms together, to circumvent their respective limitation and design a hybrid adaptively modulated FET (HamFET) that orients power saving and performance enhancement simultaneously. This transistor architecture, utilizing a nested source configuration without cost or area penalties, exhibits both ultrasteep (subthermionic) subthreshold swing and the largest “on” and “off” current ratio over the state-of-the-art tunneling transistors. Our design methodology of hybrid switching mechanism is also applicable to other mechanism, material, and architecture systems, opening the doors to a range of high-speed application opportunities for ultralow-power but performance-insufficient electronics.